(untitled) (KYAMC Journal, 2021)
Background: The purpose of these study was to find out the risk of eclampsia in relation to several demographic and anthropometric factor and to find out a way to prevent eclampsia. Objective: To find out the epidemiology of eclampsia and to reduce maternal and neonatal mortality and morbidity due to eclampsia. Materials and Methods: A cross sectional descriptive study was conducted to assess the fetomaternal outcome of eclampsia. The study was carried out at the Eclampsia unit, Dhaka Medical College Hospital, Dhaka over a period of six months from 1st July 2008 to 31st December 2008. A total of 48 patients with diagnosis of antepartum and intrapartum eclampsia were consecutively taken in the study. The test statistics used to analyse the data were descriptive statistics. Results: About 39.6% of the patients was under the age of 20 years, 43. 7% patient was between the age of 20-25 years. By occupation 77.1% patient was housewife, 17.9% patient was Garments worker and 4.1% patient was day labour. By level of education about 56.3% patient was illiterate, 29.2% patient was of primary level. About 57% of patients remained unconscious. About 7% of patients developed acute renal failure,16.7% CVA,14.6% HELLP syndrome and 39.6% pulmonary oedema. The mean hospital stay was 9.5 ± 3.3 days. Majority (93.8%) of the patients recovered while 6.3% died. Conclusion: Eclampsia is still a major cause of maternal mortality and morbidity in Bangladesh. A qualitative and quantitative improvement in prenatal consultation should make it possible to reduce incidence of eclampsia in our community. Monitoring of high-risk patients may reduce the complication rate. KYAMC Journal Vol. 11, No.-4, January 2021, Page 189-192